Asociación entre las fases del ciclo menstrual y la superficie ocular en un grupo de mujeres de 18 a 40 años de la Universidad Antonio Nariño - Flechas Sosa, Diana Yohana (Universidad Antonio Nariño, 2023)
Menstruation is a cyclical process that occurs monthly due to differentiation, proliferation and shedding of the uterine endometrium. This process is regulated by steroid hormones such as estrogen and progesterone. However, These hormonal changes can cause symptoms, such as dysmenorrhea, which is the menstrual pain that some women experience during their cycle. Furthermore, these Symptoms can affect other systems of the body, such as the digestive system and manifest with nausea, vomiting, constipation or diarrhea